TRAINING TO IMPROVE THE COMPETENCE OF 21ST CENTURY TEACHERS WITH A TECNOLOGICAL PEDAGOGICAL AND CONTENT KNOWLEDGE (TPACK) APPROACH THROUGH THE GOOGLE SITES APPLICATION AND MENTIMTER FOR CHRISTIAN HIGH SCHOOL TEACHERS 2 KALABAHI: PELATIHAN PENINGKATAN KOMPETENSI GURU ABAD 21 DENGAN PENDEKATAN TECNOLOGICAL PEDAGOGICAL AND CONTENT CNOWLEDGE (TPACK) MELALUI APLIKASI SITES GOOGLE DAN MENTIMTER BAGI GURU SMA KRISTEN 2 KALABAHI - Alboin Selly (Yayasan Education and Social Center, 2022)
Pedagogic Competence is one of the competencies that must be possessed by teachers in order to improve and encourage the success of the quality of education. Therefore, teachers have a great responsibility to continue to train and improve pedagogical competence in the industrial era 4.0 or commonly referred to as the 21st century era. 21st century learning emphasizes learning that is integrated with technology, for this reason, teachers not only master, content or teaching materials, pedagogics, but also the teacher's ability to master three components, namely, content, pedagogic and technology. Service activities in the form of training on google sites applications and mentimeters use the methods of lectures, discussions, training, guidance and evaluation. The participants involved are 42 Kalabahi Christian High School Teachers who participated in service activities, the results of the activities of Christian High School Teachers 2 can use the google site application and mentimeter in learning activities